2006
DOI: 10.1016/j.cellbi.2005.09.009
|View full text |Cite
|
Sign up to set email alerts
|

An NMR method to characterize multiple water compartments on mammalian collagen

Abstract: A molecular model is proposed to explain water 1H NMR spin-lattice relaxation at different levels of hydration (NMR titration method) on collagen. A fast proton exchange model is used to identify and characterize protein hydration compartments at three distinct Gibbs free energy levels. The NMR titration method reveals a spectrum of water motions with three well-separated peaks in addition to bulk water that can be uniquely characterized by sequential dehydration. Categorical changes in water motion occur at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 35 publications
4
58
0
1
Order By: Relevance
“…In tendons these different relaxation components provide additional information about the structure of the collagen, suggesting that the protons in the cleft of the collagen have short T 1 and are in rapid exchange with the other protons and hence act as a relaxation sink for the collagen. A similar situation is found in bone (52), where rapid exchange of magnetization is found between the solid pool of protons (associated with the backbone of the collagen) and the hydrogen-bonded protons of collagen.…”
Section: Mr Properties Of Tissuementioning
confidence: 63%
See 1 more Smart Citation
“…In tendons these different relaxation components provide additional information about the structure of the collagen, suggesting that the protons in the cleft of the collagen have short T 1 and are in rapid exchange with the other protons and hence act as a relaxation sink for the collagen. A similar situation is found in bone (52), where rapid exchange of magnetization is found between the solid pool of protons (associated with the backbone of the collagen) and the hydrogen-bonded protons of collagen.…”
Section: Mr Properties Of Tissuementioning
confidence: 63%
“…Collagen may display strong magic angle behaviour owing to the uniform orientation of the collagen fibers and the restricted motion of the protons associated with these fibers (46)(47)(48)(49)(50). This magic angle phenomenon has been used to examine the structure of the collagen itself (51,52). Collagen has multiple relaxation components that depend on the hydration of the collagen.…”
Section: Mr Properties Of Tissuementioning
confidence: 99%
“…O cálculo do valor monomolecular através da equação de BET torna-se progressivamente impreciso à medida que o valor de C se aproxima da unidade. [10] [5,6], trabalhando com colágeno de tendão bovino, por cristalografia, encontraram valores semelhantes aos nossos para o teor de umidade na camada monomolecular.…”
Section: Ajuste Das Isu Aos Modelos Matemáticos De Bet E Gabunclassified
“…Fullerton Again, it is noted that studies which seemingly agree with the notion of ice-like bonds [146,147,175,177] are carried out on fibres or fibrils, while those which disagree were concerned with a sole collagen molecule [64,65,148,181]. The key difference is the possible inclusion of intra-fibrillar water in the former.…”
Section: Water Bridges and The Magic Angle Effectmentioning
confidence: 99%
“…A summary of the research into collagen hydration, by Fullerton, can be found in [53]. Based on the hydrations calculated from NMR titration experiments [146] of tendon, Cameron and Fullerton [145] developed the Stoichiometric Hydration Model (SHM), which predicts one single and one double water bridge for every tripeptide unit in the tropocollagen molecule.…”
Section: 6 B Free and Bound Water Pools In Tissuesmentioning
confidence: 99%